Uma solução técnica, artística e sanitária: os parques urbanos e equipamentos sanitários nos projetos urbanísticos de saturnino de brito (Recife/PE, João Pessoa, PB, Natal/RN) - Morais, Janyffer Cavalcante de (2017)
The advent and expansion of the English Industrial Revolution from the mid-eighteenth century and throughout the nineteenth century had a major impact on the urban dynamics of cities, which became the main centers of population concentration and economic activity. Sanitary engineering emerged as a technical solution to the problems of urban unhealthiness, caused by accelerated urban growth unaccompanied of the necessary infrastructure. In this context, the Escritório Saturnino de Brito, founded by the engineer Saturnino de Brito in 1920, stood out in Brazil. Its Sanitation, Improvement and Expansion Plans for several brazilian cities contributed to significant changes in national urban planning. Even after the death of its founder in 1929, the Office continued its ideas and principles, under the coordination of Saturnino de Brito Filho. Among the plans elaborated by the Escritório Saturnino de Brito, the General Works Plan for Natal, RN (1935-1939) stands out in bringing the design of parks surrounding sanitary equipment, such as reservoirs and pumping stations. The association between sanitation structures and public parks, however, is something that has been around for some time, as can be seen in Olmsted projects in the United States, such as Central Park and Emerald Necklace. The interest in this type of association has been taken up in recent projects, and in view of this contemporary recovery, it seems fundamental to understand the genesis of this type of relationship. Therefore, the objective of this dissertation is to understand the relationship between sanitary facilities and parks in urban development projects for the modern Brazilian city of the early twentieth century, based on the analysis of the plans of the Escritório Saturnino de Brito. For this study we propose the analysis of concrete cases, by means of bibliographical and documentary research, choosing the work of the Escritório Saturnino de Brito for some cities in the Northeast of Brazil: Natal (RN), Recife (PE) and João Pessoa (PB). The main common element among the three plans studied is the presence of an integrated relationship between sanitary equipment and parks or squares. In Recife and João Pessoa, water elements were incorporated into the sanitary project, represented by the canals, rivers and lagoon, bringing impact to the landscape. In Natal the highlight is for the use of the reservoir areas for the creation of parks. The concern with aesthetic factors is clear, although the sanitary factors were the guiding principles of the proposals.